Distribution of volatile organic compounds over Indian subcontinent during winter: WRF-chem simulation versus observations. (September 2019) - Chutia, Lakhima; Ojha, Narendra; Girach, Imran A.; Sahu, Lokesh K.; Alvarado, Leonardo M.A.; Burrows, John P.; Pathak, Binita; Bhuyan, Pradip Kumar
Abstract: We investigate the distribution of volatile organic compounds (VOCs) over Indian subcontinent during a winter month of January 2011 combining the regional model WRF-Chem (Weather Research and Forecasting model coupled with Chemistry) with ground- and space-based observations and chemical reanalysis. WRF-Chem simulated VOCs are found to be comparable with ground-based observations over contrasting environments of the Indian subcontinent. WRF-Chem results reveal the elevated levels of VOCs (e. g. propane) over the Indo-Gangetic Plain (16 ppbv), followed by the Northeast region (9.1 ppbv) in comparison with other parts of the Indian subcontinent (1.3–8.2 ppbv). Higher relative abundances of propane (27–31%) and ethane (13–17%) are simulated across the Indian subcontinent. WRF-Chem simulated formaldehyde and glyoxal show the western coast, Eastern India and the Indo-Gangetic Plain as the regional hotspots, in a qualitative agreement with the MACC (Monitoring Atmospheric Composition and Climate) reanalysis and satellite-based observations. Lower values of RGF (ratio of glyoxal to formaldehyde <0.04) suggest dominant influences of the anthropogenic emissions on the distribution of VOCs over Indian subcontinent, except the northeastern region where higher RGF (∼0.06) indicates the role of biogenic emissions, in addition to anthropogenic emissions. Analysis of HCHO/NO2 ratio shows a NOx -limited ozone production over India, with a NOx -to-VOC transition regime over central India and IGP. The study highlights a need to initiate in situ observations of VOCs over regional hotspots (Northeast, Central India, and the western coast) based on WRF-Chem results, where different satellite-based observations differ significantly. Graphical abstract: Image 1 Highlights: First high-resolution simulation of VOCs over South Asia during winter. Extensive model evaluation against in situ, satellite data, and MACC reanalysis. Regional hotspots of enhanced VOC loadings are revealed. Significant differences in formaldehyde observed from various satellites.